Sense of security of local communities in Poland - Ciekanowski, Zbigniew; Nowicka, Julia; Wyrebek, Henryk; Perdion, Waldemar (Scientific Journal of Bielsko-Biala School of Finance and Law, 2023)
The aim of the study was to identify differences in the level of perceived safety in the Pruszków and Grodzisk districts as well as the nature of actions taken to increase the sense of security of residents in a place where until recently one of the most dangerous criminal groups in the country still operated. In order to examine the principles of human functioning in local society, the area of special interest - as a result of the exploration of the topic - was covered by the activities of two leading entities that play a particularly important function in shaping the process of local security. The analysis included evaluation of such categories as satisfactory relations with neighbors in the place of residence, permanent employment in the county, lack of crime in the county, unemployment in the county and evaluation of selected entities responsible for public safety.